The Effect Entrepreneurship Product Innovation on Business Performance in Industry Micro Food of Brown Sugar in Bonto Bahari District Bulukumba Regency - Sasmila; Muhammad Guntur; Aris Baharuddin; Aslinda; Andi Cudai Nur (Fakultas Ilmu Sosial dan Hukum, 2024)
This study aims to determine the effect of entrepreneurial product innovation on business performance in the brown sugar micro food industry in the district of Bonto Bahari, Bulukumba Regency. This study uses a quantitative approach to the type of descriptive research with a population of 30 respondents and the sample in this study as many as 30 respondents. Data collection techniques used through observation, questionnaires (questionnaire), and documentation. The data obtained from the research results were processed using data analysis and using the SPSS software application consisting of descriptive analysis techniques and inferential statistical analysis. The results of the research that can show that the indicators for each of the variables used are in the entrepreneurial product innovation variable showing that the indicators used in this study are in the good category. As for the indicators on the business performance variable, it shows in the very good category. Based on the results of the inferential analysis, it was obtained that the person correlation was 0.939, which means that there is a very strong relationship between the two variables. So it can be concluded that there is a significant influence between Entrepreneurial Product Innovation on Business Performance in the Brown Sugar Food Micro Industry in Bonto Bahari District, Bulukumba Regency.